Theoretical study on the exciton dynamics of coherent excitation energy transfer in the phycoerythrin 545 light-harvesting complex - Cui, Xue-Yan; Yan, Yi-Jing; Wei, Jian-Hua (Chinese physics B, 2022)
The experimental observation of long-lived quantum coherence in the excitation energy transfer ( EET ) process of the several photosynthetic light-harvesting complexes at low and room temperatures has aroused hot debate. It challenges the common perception in the field of complicated pigment molecular systems and evokes considerable theoretical efforts to seek reasonable explanations. In this work, we investigate the coherent exciton dynamics of the phycoerythrin 545 ( PE545 ) complex. We use the dissipation equation of motion to theoretically investigate the effect of the local pigment vibrations on the population transfer process. The result indicates that the realistic local pigment vibrations do assist the energy transmission. We demonstrate the coherence between different pigment molecules in the PE545 system is an essential ingredient in the EET process among various sites. The coherence makes the excitation energy delocalized, which leads to the redistribution of the excitation among all the chromophores in the steady state. Furthermore, we investigate the effects of the complex high-frequency spectral density function on the exciton dynamics and find that the high-frequency Brownian oscillator model contributes most to the exciton dynamic process. The discussions on the local pigment vibrations of the Brownian oscillator model suggest that the local heterogeneous protein environments and the effects of active vibration modes play a significant role in coherent energy transport.